Post-COVID-19 syndrome, who at risk and why: an insight from Qatar 2022 - Adli, Nada; Bala, Mohamed; Bougmiza, Mohamed Iheb; Al-Kuwari, Mohamed Ghaith; Al-Khenji, Abdul Hameed; Selim, Nagah (Frontiers in Public Health, 2024)
Background: Despite the recovery from the COVID-19 pandemic, many people experience post-COVID-19 syndrome, which negatively impacts their health and function. This condition has become a significant public health problem that requires immediate attention.Objective: To study the prevalence, clinical characteristics, and predictors of post-COVID-19 Syndrome in Qatar during 2022.Methods: An analytic cross-sectional study was conducted among COVID-19 confirmed cases from January 2022 to July 2022 in Qatar. A simple random sample was employed to include (n=588) participants from the list of cases and invited to participate in a telephone survey. The World Health Organization's standard case definition for PCS was adopted.Results: Out of 368, the prevalence of post-COVID-19 syndrome was 43.2% (n=159). Most PCS cases were females (67.9%; n=108), married (73.6%; n=117), and university and higher educational level (83.6% n=133). However, 78.7% (n=125) reported poor to moderate levels of social support. Only 30.2% (n=48) of PCS patients had a history of chronic diseases, and 5.7% (n=9) required hospital admission during acute illness.Among PCS cases, the most commonly reported symptoms were fatigue (75.5%), followed by anxiety (49.1%), forgetfulness (46.5%), mood alteration (45.3%), and general weakness (39.6%). The logistic regression revealed that female gender (AOR: 2.58 95%CI: 1.58-4.225, p<0.0001), university and high educational level (AOR: 2.2, 95%CI: 1.256-3.98, p<0.006), poor level of social support (AOR: 2.45; 95%CI: 1.55-4.13; p< 0.002), were significant predictors for PCS.Post-COVID-19 syndrome may go under-recognized. More efforts are needed to raise awareness and mobilize the resources to respond to this ongoing public health problem.